Twenty-Five Years of Domoic Acid Monitoring in Galicia (NW Spain): Spatial, Temporal and Interspecific Variations - Juan Blanco (MDPI AG, 2021)
Prevalence, impact on shellfish resources and interspecific, spatial, and temporal variabilities of domoic acid (DA) in bivalves from Galicia (NW Spain) have been studied based on more than 25 years of monitoring data. The maximum prevalence (samples in which DA was detected) (100%) and incidence (samples with DA levels above the regulatory limit) (97.4%) were recorded in Pecten maximus, and the minimum ones in Mytilus galloprovincialis (12.6 and 1.1%, respectively). The maximum DA concentrations were 663.9 mg kg−1 in P. maximus and 316 mg kg−1 in Venerupis corrugata. After excluding scallop P. maximus data, DA was found (prevalence) in 13.3% of bivalve samples, with 1.3% being over the regulatory limit. In general, the prevalence of this toxin decreased towards the North but not the magnitude of its episodes. The seasonal distribution was characterized by two maxima, in spring and autumn, with the later decreasing in intensity towards the north. DA levels decreased slightly over the studied period, although this decreasing trend was not linear. A cyclic pattern was observed in the interannual variability, with cycles of 4 and 11 years. Intoxication and detoxification rates were slower than those expected from laboratory experiments, suggesting the supply of DA during these phases plays an important role.